2-DOF dynamic model of vibro-compactor used for the carbon anodes block production. (August 2017) - Rebaïne, Fatma; Bouazara, Mohamed; Marceau, Daniel; Kocaefe, Duygu; Coulombe, Patrick
Graphical abstract: Highlights: The developed dynamic model of the vibro-compactor simulates the accelerations. The acceleration is an important parameter that can be used to diagnose problems. The difference between predicted and measured rod accelerations decreased by 81%. The rod acceleration can be controlled by varying the balloon pressure. The model obtained is directly applicable to the industry. Abstract: The vibro-compaction is the most common technology employed for the formation of green carbon anodes in the primary aluminum industry. The acceleration is an important parameter used to predict the performance of the equipment. In this paper, a dynamic model of the vibro-compactor with two degrees of freedom is developed. The dynamic model simulates the acceleration of vibration table, the guide rod and the changes in various vibro-compaction parameters. Subsequently, an experimental method was established for measuring the dynamic rigidity of anode paste. The developed model gives a good approximation of acceleration compared with those obtained by experimental tests.